The role of human glucagon-like peptide-1 analog in therapy of type 2 dianetes mellitus - Marina Vladimirovna Shestakova (Endocrinology Research Centre, 2010)
The first human glucagon-like peptide-1 analog (liraglutide) was registered in Russia in May 2010. This review contains data on the results of randomizedclinical studies of this preparation applied to the treatment of patients with DM2 as monotherapy and in combination with traditional hypoglycemicagents (LEAD 1-6 program). Liraglutide is shown to have advantages when used by patients with an excess body mass and obesity, those atrisk of cardiovascular diseases and prone to develop hypoglycemia. Patients treated with liraglutide (1.8 mg) more frequently achieved the desired efficacyendpoints (НbА1с < 7%, reduced body mass and AP control) of than those using traditional therapy (24 vs 3-14%).